Ichthyodiversity in southeastern Arabian Peninsula: Annotated checklist, taxonomy, short description and distribution of Inland fishes of Oman - Esmaeili, Hamid Reza; Jufaili, Saud Al; Masoumi, Amir Hassan; Zarei, Fatah (Zootaxa, 2022)
Oman, a country in Southwest Asia, situated on the southeastern quarter of the Arabian Peninsula presents a high level of biological diversity especially marine elements. Although arid habitats cover most parts of Oman (82%), the region has several freshwater systems that are vital for the survival of people as well as for different groups of animals and plants. Research works on Oman biodiversity including terrestrial and marine, have been steadily increasing over the last few decades, but freshwater ecosystems have not been well investigated. Oman comprises parts of three freshwater ecoregions including the Oman Mountains, Southwestern Arabian Coast, and Arabian Interior having xeric freshwaters and endorheic (closed) basins which support a variety of inland fishes. The current checklist provides for each species of inland waters of Oman all recognized and named taxa, documenting recent changes and controversies in nomenclature, its records, taxonomic status, synonyms, etymology, common English name, short description, range expansion, and detailed distribution map based on several field surveys throughout the country. We also provide native, endemic, and introduced species. The diversity of inland fishes of Oman included in this annotated checklist consists of 23 recognized species in 15 genera, 10 families, seven orders, and a class. Also, for the first time, we report and confirm the presence of four species in the inland waters of Oman. The most diverse order is Cypriniformes (nine species, 39.13%), followed by Gobiiformes (six species, 26.09%), Cyprinodontiformes (three species, 13.04%), Cichliformes (two species, 8.69%), and Centrarchiformes, Gonorynchiformes and Mugiliformes (one species, 4.35% each). 21 native species (91.3%) in nine families and two exotic species (8.7%) in two families are listed here. Out of 21 native species, eight species (16.8%) in two families are endemic elements that are restricted to the Oman territory only. Identification of all recognized species was confirmed by DNA barcoding (mitochondrial COI). Oman Mountains Ecoregion (OME), Southwestern Arabian Coast Ecoregion (SACE), and Arabian Interior Ecoregion (AIE) harbor 15, 12, and one species, respectively. The provided data will be necessary for increasing the fish knowledge, the development of competent and pragmatic management plans and effective conservation policies.